Characterization of novel CD55 isoforms expression in normal and neoplastic tissues. Issue 1 (21st May 2013) - Vainer, E. D.; Meir, K.; Furman, M.; Semenenko, I.; Konikoff, F.; Vainer, G. W.
Abstract CD55 (decay‐accelerating factor, DAF) is overexpressed in several types of cancer, including colorectal cancer. Because of its inhibitory effect on the complement system, it has been suggested as a possible target for cancer immunotherapy. However, CD55 is also expressed in normal tissues, body fluids and stroma, limiting the use of anti‐CD55 therapeutic antibodies. Two novel CD55 splice variants or isoforms have recently been identified. These have been shown to contain part or all of intron 7 (CD55int7+), in contrast to the previously identified splice variants (CD55wt), which do not contain intron 7. Our aim was to determine the pattern of expression of the CD55int7+ isoforms in normal and cancer tissues and to compare it to CD55wt. We found that while CD55's isoforms levels vary directly, CD55wt is much more abundant (on average 48 times more) than CD55int7+. Moreover, colon cancers that express high CD55wt mRNA levels tend to upregulate CD55int7+ to a further extent. Finally, we compared the protein levels of CD55int7+ to CD55wt by immunohistochemistry in various colorectal pathological conditions including neoplasia, and found that the levels of both isoforms were elevated in all types of colonic pathology. These results show that the levels of CD55int7+ in normal tissue are much lower than CD55wt, while in tumors it is restricted to the epithelial structures unlike CD55wt. Thus, CD55int7+ may be a more suitable target for cancer immunotherapy.